Relations between Spectrum Curves of Discrete Sturm-Liouville Problem with Nonlocal Boundary Conditions and Graph Theory. II - Vitkauskas, Jonas; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2021)
In this paper, relations between discrete Sturm–Liouville problem with nonlocal integral boundary condition characteristics (poles, critical points, spectrum curves) and graphs characteristics (vertices, edges and faces) were found. The previous article was devoted to the Sturm–Liouville problem in the case two-points nonlocal boundary conditions.